Utility of indocyanine green fluorescent dye in emergency general surgery: a review of the contemporary literature - Khalaf, Mohamed H.; Abdelrahman, Husham; El-Menyar, Ayman; Afifi, Ibrahim; Kloub, Ahmad; Al-Hassani, Ammar; Rizoli, Sandro; Al-Thani, Hassan (Frontiers in Surgery, 2024)
For decades, indocyanine green (ICG) has been available for medical and surgical use. The indications for ICG use in surgery have expanded where guided surgery directed by fluorescence and near-infrared fluorescent imaging offers numerous advantages. Recently, surgeons have reported using ICG operative navigation in the emergency setting, with fluorescent cholangiography being the most common procedure. The utility of ICG also involves real-time perfusion assessment, such as ischemic organs and limbs. The rising use of ICG in surgery can be explained by the ICG's rapid technological evolution, accuracy, ease of use, and great potential to guide precision surgical diagnosis and management.The review aims to summarize the current literature on the uses of ICG in emergency general surgery. It provides a comprehensive and practical summary of the use of ICG, including indication, route of administration, and dosages. To simplify the application of ICG, we subdivided its use into anatomical mapping and perfusion assessment. Anatomical mapping includes the biliary tree, ureters, and bowel. Perfusion assessment includes bowel, pancreas, skin and soft tissue, and gonads. This review provides a reference to emergency general surgeons to aid in implementing ICG in the emergency setting for more enhanced and safer patient care.